2014
DOI: 10.1007/s00276-014-1273-y
|View full text |Cite
|
Sign up to set email alerts
|

Right gastroepiploic artery arising from the dorsal pancreatic artery: a very rare anatomic variation underlying interesting embryologic implications

Abstract: The exceptional case of the right gastroepiploic artery (RGE) arising from the dorsal pancreatic (DP) artery in an individual affected by hepatocellular carcinoma is presented. This anatomic variant was demonstrated with a selective angiography of the common hepatic artery that showed a distinct DP artery branching from the injected artery. The DP artery gave off regular pancreatic branches and continued as a long and winding vessel that was identified as the RGE by its general course, the anterior epiploic br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Gregorio FD et al found that the RGEA originated from the dorsal pancreatic artery, and Sakamoto H et al reported that the RGEA originated from the superior mesenteric artery. 21,22 In our study, the RGEA of all 50 patients in the CAS group originated from the GDA without any variation. However, there were obvious differences in the diameters of the RGEA; therefore, we divided the patients into a coarse blood supply type and a fine blood supply type.…”
Section: Variation Analysis Of the Infrapyloric Vesselsmentioning
confidence: 66%
“…Gregorio FD et al found that the RGEA originated from the dorsal pancreatic artery, and Sakamoto H et al reported that the RGEA originated from the superior mesenteric artery. 21,22 In our study, the RGEA of all 50 patients in the CAS group originated from the GDA without any variation. However, there were obvious differences in the diameters of the RGEA; therefore, we divided the patients into a coarse blood supply type and a fine blood supply type.…”
Section: Variation Analysis Of the Infrapyloric Vesselsmentioning
confidence: 66%